THE EFFECT OF URBANIZATION AND ECONOMIC GROWTH ON THE ENVIRONMENT IN THE EMERGING MARKETS (Third Sector Social Economic Review, 2021)
The present study aims to determine the effect of urbanization and economic growth in selected emerging market economies (Argentina, Brazil, China, India, Indonesia, Mexico, Poland, Russia, S. Africa and Turkey) on the environment. The study covers the years from 1990 to 2016 and includes a panel cointegration analysis. After that, the long-term predictions were estimated with the panel augmented mean group (AMG) estimator. As a result of the analysis, it was found that there is a positive relation of both economic growth and urbanization with the volume of carbon emissions. This reveals that economic growth and increasing urbanization have a negative effect on the environment. According to the panel AMG estimator, an increase of 1 unit in economic growth increases the amount of carbon emissions by 0.73 unit. In addition, it was determined that the effect of urbanization on the environment is more dominant. As a result of the analysis, it was determined that an increase of 1 unit in the level of urbanization increased carbon emissions by 1.16 units.
Keywords: Urbanization; Economic Growth; CO2 emissions